Exploring power dynamics and bricolage practices in diverse cases of marine resource conflicts - Saunders, Fred; Prado, Deborah; Knol-Kauffman, Maaike; Sowman, Merle; Tafon, Ralph; Gilek, Michael (Frontiers in Ocean Sustainability, 2025)
Economic growth strategies grounded in blue economy narratives are intensifying and proliferating marine conflicts. In light of this, the study explores how local actors employ bricolage—improvised, resourceful strategies—to challenge institutional norms and reconfigure power relations in the context of marine resource conflicts. We introduce a bricolage power framework to analyze marine conflict in Norway, Brazil, and South Africa. The study shows that fishers, working with NGOs and other partners, are actively engaged in amplifying their voices, promoting accountability, and seeking more just and sustainable ways to manage conflict. These insights emphasize the importance of collective action and collaborative partnerships to change conflict relations and outcomes by challenging various institutional practices and dominant power structures. In particular, the Brazilian and South African cases demonstrate how marginalized actors, through creative bricolage practices, can adapt and reinvent regulatory processes to challenge unjust practices and foster more inclusive and adaptive governance structures. While the grassroots initiatives examined show promise, they remain fragmented and have yet to catalyze systematic institutional transformation in the cases analyzed, so we are cautious against overestimating the transformative potential of these efforts.